(The Effect of Cultur Supplement Mixing on Cocoa Beans Fermentation Period) - Yumas, Medan; Thamrin, Imran (Warta Industri Hasil Pertanian, 2010)
The research of mixing culture supplement on cocoa beans fermentation period has been conducted. The aim of this research is to know the effect of composite culture additive fermented period. The variable in this treatment covered are temperature, acidity, poliphenol, reduction sugar, fermentation index, and sensoric test. The process of fermentation was used to cocoa bean natural incubated. Cocoa bean was added with mixing culture (Saccharomyces cerevisiae Lactobacillus casei, Acetobacter aceti and Bacillus subtilis) in water (nutrient broth). This treatment as well as was compare with natural fermentation and fermentated process through the activator adding. The period of fermentation are2,3,4,5 and 7 days. The research result shown that the optimum of period fermented was found in three days on treatment mixing culture supplement with fermentation index i.e. 1.0704, optimum temperature i.e. 49 derajat C, acidity i.e. 5.25, poliphenol i.e. 2.52% and reduction sugar i.e. 4.13%.